Hydrothermal pretreatment improves humification in co-composting of oil palm fronds and paper mill sludge. Issue 3 (June 2022) - Huang, Wenfeng; Wen, Ping; Wang, Weiwu; Liu, Xiaoming; Wang, Yueqiang; Yu, Zhen; Li, Youming; Hou, Yi; Zhou, Shungui
Abstract: The co-composting of oil palm fronds and paper mill sludge may be economical and eco-friendly, yet the complex indigenous configuration of lignocellulose reduces the bioavailability of waste, resulting in the hindrance to the humification process. In this work, oil palm fronds after hydrothermal pretreatment were mixed with paper mill sludge for co-composting, and the effect of hydrothermal pretreatment on the humification process was explored using excitation-emission matrix-parallel factor analysis and 16S rDNA sequencing. The results showed that the duration of thermophilic phase was extended from 13 days to 17 days after hydrothermal pretreatment. During hydrothermal-pretreated composting, the consumption of protein-like substances and the production of humus-like substances increased by 24.7% and 33.9%, respectively, compared with those of control. The degradation of polysaccharide (decreased from 76.5 to 20.0 g/kg) was accelerated and the content of reducing sugar (ranged from 11.5 to 13.5 g/kg) was increased. The key microbial communities (including Bacillaceae, Sphingobacteriaceae, Streptosporangiaceae and Thermonosporaceae ) showed obviously stronger activity. Correlation analysis showed that the production of reducing sugar and the activity of key microbial communities were reinforced, and both were favorable for the rapid synthesis of humus. Collectively, this work provides an overview of a regulatory mechanism underlying humus formation during the composting of lignocellulosic wastes. Graphical Abstract: ga1 Highlights: HP of OPF was applied to their co-composting with PMS. HP significantly improved the humification process during co-composting. RS content and key microbial communities' activity contributed to humus formation.